SINGLE PLANE MIMO ANTENNA FOR 5G DEVICES - BOIKO, JULIY; KARPOVA, LESYA; SEMENYUK, VITALIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This work presents the design of a single-plane multiple-input/multiple-output MIMO antenna system for smartphones with 5G support at a frequency below 6 GHz. The developed MIMO antenna consists of four loop-shaped emitters located at each corner of the mobile phone board, which conforms to the principle of pattern diversity. The single-antenna element resonates at 3.5 GHz, has an impedance bandwidth of 1.28 GHz (3-4.28 GHz) for S11 ≤ –6 dB, and is 720 MHz (3.18-3.9 GHz) for S11 ≤ –10dB. For a single-antenna element, a peak gain of 3.64 dBi is observed with an antenna efficiency of >90%. For the MIMO antenna configuration, isolation >10 dB is achieved between its elements. In addition, the designed MIMO antenna provides sufficient radiation coverage to support different sides of the mobile phone board, which is an important feature for all 5G-enabled phones. A planar multiple-input/multiple-output MIMO antenna design is presented for sub-6 GHz 5G-enabled mobile phone applications. Four loop-shaped radiators are designed at each corner of a smartphone board, and they all follow the design configuration of pattern diversity. Several MIMO antenna features are evaluated, such as S-parameters, gain patterns, radiation and total efficiency, envelope correlation coefficient, total active reflection coefficient, and diversity gain. From the reported results, it may be concluded that the presented MIMO antenna system successfully meets the criteria of 5G-enabled mobile phones. In addition, the impacts of human hands and heads on MIMO antenna performance are investigated, and acceptable performance in the data and conversation modes is observed.